2017
DOI: 10.3389/fphar.2017.00163
|View full text |Cite
|
Sign up to set email alerts
|

IL-1 Inhibition May Have an Important Role in Treating Refractory Kawasaki Disease

Abstract: Kawasaki disease (KD) is an acute inflammatory vasculitis occurring in young children before 5 years and representing at this age, the main cause of acquired heart disease. A single infusion of 2 g/kg of intravenous immunoglobulins along with aspirin has reduced the frequency of coronary artery aneurysms from 25 to 5%. However, 10–20% of patients do not respond to standard treatment and have an increased risk of cardiac complications and death. The development of more potent therapeutic approaches of KD is an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 41 publications
3
40
0
Order By: Relevance
“…These observations further support that interventions blocking IL-1β and its receptor could be more broadly utilized as a front-line agent to treat KD, a concept that is now readily entertained [6,7]. These observations further support that interventions blocking IL-1β and its receptor could be more broadly utilized as a front-line agent to treat KD, a concept that is now readily entertained [6,7].…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…These observations further support that interventions blocking IL-1β and its receptor could be more broadly utilized as a front-line agent to treat KD, a concept that is now readily entertained [6,7]. These observations further support that interventions blocking IL-1β and its receptor could be more broadly utilized as a front-line agent to treat KD, a concept that is now readily entertained [6,7].…”
Section: Discussionmentioning
confidence: 57%
“…In summary, while IL-1Ra is now in two Phase II clinical trials in IVIG-non-responsive acute KD patients, our findings indicate a potential benefit of IL-1 receptor blockade on the long-term cardiovascular consequences of KD by inhibiting acute KD myocarditis and cardiac dysfunction. These observations further support that interventions blocking IL-1β and its receptor could be more broadly utilized as a front-line agent to treat KD, a concept that is now readily entertained [6,7].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…A single infusion of 2 gm/kg of intravenous immunoglobulins (IVIGs), administered in conjunction with aspirin, has reduced the frequency of coronary artery aneurysms in patients with KD from 25% to 5%. However, 10–20% of patients are unresponsive to IVIG treatment, and thus present with persisting fever and inflammation and have an increased risk of cardiac complications and death .…”
Section: Introductionmentioning
confidence: 99%
“…Initial reports suggesting these drugs are safe to children but data regarding their efficacy is still not available [32]. In a study conducted by Dusser P et al [33] IL-1 blockade treatment such as anakinra showed successful improvement in myocarditis and aneurysm that was formed in a mouse model of KD.…”
Section: Interleukin-1 (Il-1) Inhibitionmentioning
confidence: 99%